Inkonsistensi Norma Penempatan Tentara Nasional Indonesia Sebagai Penjabat Kepala Daerah Pada Masa Transisi - Agung Barok Pratama (Lembaga Pengembangan Kinerja Dosen, 2024)
The holding of simultaneous regional elections in 2024 and the postponement of regional elections from 2022 due to the expiration of the term of office result in the threat of vacancies in positions, especially positions as regional heads in Indonesia. To fill the vacancy, an acting regional head is appointed until a definitive regional head is elected in the simultaneous regional elections in 2024. The problem is that those appointed as acting officers are apparently from active TNI elements, this is of course contrary to the spirit of reform which wants to eliminate dual functions as regulated in the TNI Law. The aim of the research is to find consistency in norms in the appointment of active TNI officers and their juridical implications. This research is normative using a statutory and conceptual approach. The research results show that consistency between these norms is needed in regulating these appointments, considering that civilian positions can only be filled by TNI soldiers who have resigned or retired from active military service, in accordance with the required competencies and through an open and competitive selection process. This step is important to ensure the maintenance of TNI neutrality and professionalism, compliance with the law, and respect for the principles of reform.